2021
DOI: 10.1002/cptc.202100098
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable Circular Caged Oligonucleotides for Transcriptome In Vivo Analysis (TIVA)

Abstract: Light activation is an effective way to impart spatiotemporal control over oligonucleotide probes that are widely applied for gene expression regulation and target function investigation. Among the major oligonucleotide caging strategies, cyclization with a photocleavable linker is an elegant design, which affords both atom efficiency and stability in many biological environments. Here, we introduce an improved protocol for circular oligonucleotide synthesis requiring only one round of HPLC purification. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…After 2 h, the azide-modified product was purified with a NAP-5 column (GE Healthcare). The stem loop ligation follows from prior studies , and was adapted from a previously published protocol . A premixed solution of CuSO 4 (10 equiv, 10 mM in H 2 O) and THPTA (100 equiv, 100 mM in H 2 O) was diluted to 100 μM with 10 mM Tris–Cl (pH 7.5) and H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…After 2 h, the azide-modified product was purified with a NAP-5 column (GE Healthcare). The stem loop ligation follows from prior studies , and was adapted from a previously published protocol . A premixed solution of CuSO 4 (10 equiv, 10 mM in H 2 O) and THPTA (100 equiv, 100 mM in H 2 O) was diluted to 100 μM with 10 mM Tris–Cl (pH 7.5) and H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…However, we found that it was not successful to enzymatically cyclize such phosphorothioated ODNs even with one or two normal phosphates at two terminals (data not shown). Previously, Dmochowski’s , and Frank Seela’s have improved the great potential of copper­(I)-catalyzed azide-alkyne cycloaddition (CuAAC) in terminal ligation of oligonucleotides. Therefore, we developed another efficient chemical conjugation strategy to prepare small c-ODNs (chemically modified or unmodified) based on CuAAC through intramolecular cross-linking.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Among more than 48,860 different mature microRNAs (miRBase), miR 21 is one of the most well-known and most studied onco-miRNAs, which is upregulated in many cancers. In addition, miR 21 also plays an important role in cardiovascular disease, immune response, and organ fibrosis. , miR 222 is another common onco-miRNA, which significantly increases cell proliferation. , Previous studies have applied antisense microRNA oligonucleotides against miR 21 and miR 222 to reduce tumors in vivo . However, few effective studies were investigated to reduce their possible off-target effects. Due to the specific topology of circular oligonucleotides, they have been reported to regulate and/or evaluate oligonucleotide confirmation and gene functions. Herein, we reported a new strategy to develop small circular AMOs and specifically mediate microRNA inhibition. The circular topology of circular AMOs is expected to greatly reduce general off-target effects of ODNs as well as decrease their nonspecific immunological responses and interspecies crossing.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54] It was reported that the cyclization of oligonucleotides often was accompanied by dimerization or cyclodimerization as the ring size varied. [55][56][57] Hence, these macrocyclizations usually had to be performed under high dilution conditions. Interestingly, it was found that the covalent condensation proceeded smoothly at 75 μM with almost same rates despite the different ring sizes of these two crRNAs (22 nt and 16 nt, respectively) (Fig.…”
Section: Design Synthesis and Characterization Of Photoactivatable Ci...mentioning
confidence: 99%